2017
DOI: 10.1038/s41598-017-06942-1
|View full text |Cite
|
Sign up to set email alerts
|

A Cryosectioning Technique for the Observation of Intracellular Structures and Immunocytochemistry of Tissues in Atomic Force Microscopy (AFM)

Abstract: The use of cryosectioning facilitates the morphological analysis and immunocytochemistry of cells in tissues in atomic force microscopy (AFM). The cantilever can access all parts of a tissue sample in cryosections after the embedding medium (sucrose) has been replaced with phosphate-buffered saline (PBS), and this approach has enabled the production of a type of high-resolution image. The images resembled those obtained from freeze-etching replica electron microscopy (EM) rather than from thin-section EM. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Previous studies have shown little impact on the mechanical properties on freezing tissue 46 . However, working with frozen tissues has several advantages, and different AFM studies used fresh-frozen clinical specimens 27,[47][48][49][50] . Furthermore, frozen tissue allows to prepare semithin sections, which allows histological analysis and correlation with histological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown little impact on the mechanical properties on freezing tissue 46 . However, working with frozen tissues has several advantages, and different AFM studies used fresh-frozen clinical specimens 27,[47][48][49][50] . Furthermore, frozen tissue allows to prepare semithin sections, which allows histological analysis and correlation with histological examination.…”
Section: Discussionmentioning
confidence: 99%
“…During electron microscopy studies of fixed cells the samples are protected from ambient contamination but at the cost of losing soluble cell contents 11 . Consequently, an alternative method is required, which leverages recent advances in instrumentation, preserves cellular morphology and simultaneously detects subcellular topological features without the requirement for multistep sample preparation procedures as in cryosectioning for AFM based cellular imaging 13 . Such a facile and robust methodology will have a direct impact on clinical level screening of pathological diseases 14 characterised by cell structure malfunction, e .…”
Section: Introductionmentioning
confidence: 99%
“…C. elegans 32 ) but suffered from specific limitations concerning embedding resins remaining in the analyzed sections, deeming the application of a topographical technique like AFM especially difficult. Cryo-sectioning techniques have also been applied in some studies to elucidate internal features of tissues by AFM 33 , 34 . These techniques altogether suffered to a certain extend from being experimentally highly complex concerning the sample preparation as well as the needed expensive machinery e.g.…”
Section: Discussionmentioning
confidence: 99%